An analysis of the learning curve for robotic‐assisted mitral valve repair. Issue 2 (5th January 2021) - Güllü, Ahmet Ü.; Senay, Sahin; Kocyigit, Muharrem; Zencirci, Ertugrul; Akyol, Ahmet; Degirmencioglu, Aleks; Karakus, Gultekin; Ersin, Egemen; Karabiber, Alara; Alhan, Cem
Abstract: Background: Many cardiac surgeons receive training for sternotomy‐based cardiac surgical operations in residency programs and only a few education programs offer training specifically in minimally invasive cardiac surgery. In this report, we aimed to search and analyze the learning curve for robotic‐assisted mitral valve (MV) repair in cardiac surgeons. Method: Between January 2010 and July 2019, 60 robotic‐assisted isolated MV repair surgeries were performed with DaVinci Robotic Systems in our center. Different kinds of surgical techniques were used. The assessment of the learning curve was based on cardiopulmonary bypass (CPB) and transthoracic aortic clamp (CC) times. Result: There were 23 (38.3%) men and 37 (61.7%) women with a mean age of 48.3 years. The lesions of the MV were posterior leaflet prolapsus ( n = 42, 70.0%), anterior leaflet prolapsus ( n = 8, 13.3%), Barlow disease ( n = 3, 5%), and annular dilatation ( n = 7, 11.6%). The patients underwent notochordal implantation ( n = 27, 45%), quadrangular or triangular resection ( n = 23, 38.3%), isolated ring annuloplasty ( n = 7, 11.7%), resection, and leaflet reduction ( n = 2, 3.3%) or edge to edge repair ( n = 1, 1.7%). The maturation of the learning curve appeared to be about 30 cases. The statistical analysis showed that the mean CPB and CC times for the first 30 cases were greater compared with the 30 after learning curve (155.3 vs. 118.9 min [ p = .00], 102.3 vs. 80 min [ p = .00], respectively). There was no case of conversion to open surgery. No perioperative mortality was observed. Conclusion: The maturation of the learning curve for robotic‐assisted MV repair appeared to be about 30 cases in our group of patients. This study had encouraging results for surgeons who desire to start a robotic mitral surgery program.